2023
DOI: 10.1155/2023/2885769
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Unhealthy Food Consumption and Impaired Glucose Metabolism among Adults with Overweight or Obesity: A Cross-Sectional Analysis of the Indonesian Population

Abstract: Background. It has been shown that dietary patterns are associated with glucose control. However, the association between the types of food consumed and blood glucose in overweight or obese individuals is still unclear. The present study aimed to determine the association between unhealthy food consumption and impaired glucose metabolism in adults with overweight or obesity. Methods. The analysis presented in this study was based on the data from a population-based, cross-sectional, nationally representative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The similar trend was observed in the study conducted among 8752 adult Indonesian Population who were overweight or obese, where the intake of sweet, grilled, and processed foods was associated with IFG. Moreover, it was also found that impaired glucose tolerance (IGT) was associated with the intake of high-fat foods [ 31 ]. Similar results were observed in the study conducted among 7555 Chinese adults, where the association between dietary patterns and prediabetes was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…The similar trend was observed in the study conducted among 8752 adult Indonesian Population who were overweight or obese, where the intake of sweet, grilled, and processed foods was associated with IFG. Moreover, it was also found that impaired glucose tolerance (IGT) was associated with the intake of high-fat foods [ 31 ]. Similar results were observed in the study conducted among 7555 Chinese adults, where the association between dietary patterns and prediabetes was analyzed.…”
Section: Discussionmentioning
confidence: 99%